Congenital Heart Diseases in Pregnancy - Nuswil Bernolian; Radiyati Umi Partan; Siti Nurmaini; Cindy Kesty; Benedictus Wicaksono Widodo (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
This research aims to shed light into congenital heart diseases, the pathophysiology, and the ultrasonographic findings of congenital heart diseases. Congenital heart diseases are a major health concern, affecting 1.35 million children born every year. Ventricular septal defect, atrial septal defect, and atrioventricular septal defect are found in 57.9% cases of congenital heart diseases. The risk factors include consanguineous marriage, family history of congenital heart diseases, old maternal and paternal age, and exposure to teratogens, and genetic factors. Missteps in cardiac development are the main pathophysiology of congenital heart diseases. Ultrasonography screening in 18–22 weeks gestational age is utilized to screen. Follow-up screening can increase detection rate to 80%. This study has limitation of only discussing most common congenital heart diseases and did not delve into rarer types of congenital heart diseases and did not discuss impacts or burden of congenital heart diseases in adulthood and health comorbidities associated. This literature review is beneficial for general practitioners and obstetricians focusing in maternal fetal medicine.